Literacy and the workplace revolution: a social view of literate work practices in Industry 4.0. Issue 6 (2nd November 2021) - Farrell, Lesley; Newman, Trent; Corbel, Christopher
ABSTRACT: The Fourth Industrial Revolution is widely acknowledged as a digital technological revolution building on the convergence of Robotics, the Internet of Things, and the Internet of Services. What is less often acknowledged is that it is also a revolution in the social practice of work. Literacy is a core social technology of work and it is changing as rapidly and radically as the digital technologies that are reshaping work, workers and working. This article is concerned with this new generation of workplace literacy practices as they shape, and are shaped by, the Fourth Industrial Revolution – what we call Literacy 4.0. We explore two related fields of inquiry. The first is research related to the impact of technology on work practice, work organization, and employment in a period sometimes called the Fourth Industrial Revolution. The second is research about literacy, specifically workplace literacy. In this paper we argue that it is necessary to take account of each of these fields of inquiry if we are to better understand how the next generation of workplace literacy practices is emerging and helping to constitute the Fourth Industrial Revolution.